O'Brien, Aloysius 7. Interview about the geograpy around the farm and the farming work - Shawyer; Jo (1992)
Aloysius talked about the names of pastures and roads around the farm He then talked about the work of hay making and hay cock building. "00:00 – 05:00 names of grazing area; the names of the land 05:00 -10:00 the names of the roads, marsh; blanket bogs on the hills; 10:00- 15:00 the names of marsh; the geography of the pasture area 15:00-20:00 big fire; sheep on hills 20:00-25:00 Sheep in Ireland; Irish; Irish and Newfoundlanders; 25:00 -30:00 hay cutting; tools for hay making 30:00 -35:00 hay cock; voluntary labor for hay making 35:00-40:00 hay cock building 40:00- - 49:40 horse working; hames, reins and collar for horse "